The detrimental effects of smoking on the course and outcome in adults with bipolar disorder—A narrative review - Grunze, Anna; Mosolov, Sergey; Grunze, Heinz; Born, Christoph (Frontiers in Psychiatry, 2023)
Background: Smoking is a substantial and avoidable risk for physical disability and premature death. Despite a declining tobacco use in the community of developed countries, smoking remains abundant in people with mental disorders. This narrative review highlights the epidemiology, consequences and treatment options of tobacco use disorder (TUD) and nicotine dependence (ND) in people with bipolar disorder (BD). Methods: The authors conducted a Medline literature search from 1970-November 2022 using MeSH terms “bipolar disorder”” x “smoking” or “nicotine” or “tobacco” that retrieved 770 results. Search results were complemented by additional literature retrieved from examining cross references and by hand search in text books. Finally, 92 references were considered as essential and selected for the educational purpose of this review, Summary of findings: Lifetime and point prevalence of smoking in people with BD is in the range of 45-70% and thus about 2-3 times more frequent in BD than in community samples. Smoking, TUD and ND have a detrimental impact both on mental and physical health as well as mortality in people with BD. In the absence of large controlled studies in comorbid BD and TUD or ND, pharmacological treatment follows the individual guidance for each disorder. Community-based psychosocial interventions for TUD and ND appear to be suitable in people with BD, too, as well as Cognitive Behavioural (CBT) or Acceptance and Commitment (ACT) based psychotherapies. Conclusions: Smoking is a modifiable risk factor causing increased risks both for mental and physical health in BD, and deserves more attention in treatment. More treatment research into pharmacological and psychosocial interventions in comorbid BD and TUD or ND are still needed to deliver evidence-based recommendations to physicians.